Triglyceride-glucose index: a surrogate marker of homeostasis model assessment of insulin resistance to predict diabetic nephropathy - Khan, Sania; Shazia Qayyum; Khan, Muhammad Nadim Akbar (Journal of the Pakistan Medical Association, 2024)
Objectives: To determine the association of triglyceride-glucose index with homeostasis model assessment of insulin resistance in type 2 diabetes mellitus patients, and to determine the association of triglyceride-glucose index with urinary albumin-to-creatinine ratio for predicting diabetic nephropathy. Method: The observational, cross-sectional study was conducted from September 2021 to September 2022 at the Department of Chemical Pathology, Pakistan Railway Hospital, Rawalpindi, Pakistan and comprised recently-diagnosed type 2 diabetes mellitus patients. Recorded data included age, gender, vitals, diabetes duration, body mass index and other pertinent demographic and clinical information. Measurements included spot urine albumin-to-creatinine ratio, triglyceride-glucose index, homeostasis model assesment of insulin resistance as well as fasting serum insulin, fasting plasma glucose, glycosylated haemoglobin, triglycerides, total cholesterol and serum creatinine. On the basis of triglyceride-glucose index scores, the participants were divided into 4 quartiles; Q1=4.5-5, Q2=5.1-5.5, Q3=5.6-6, and Q4=>6. Data was analysed using SPSS 26. Results: Of the 218 patients, 141(64.7%) were females and 77(35.3%) were males. The overall mean age was 49.22±11.46 years. There were 102(46.8%) overweight patients, 33(15.1%) obese and 82(37.2%) had normal weight. There were 58(26.6%) patients in Q1, 86(39.4%) in Q2, 46(21.1%) in Q3 and 28(12.8%) in Q4. Those in Q4 showed elevated fasting plasma glucose, glycated haemoglobin, triglycerides, total cholesterol, low-density lipoprotein cholesterol, homeostasis model assessment of insulin resistance and urine albumin-to-creatinine ratio (p<0.05), as well as low values for high-density lipoprotein cholesterol and estimated glomerular filtration rate(p<0.05). Fasting serum insulin was negatively linked to glycated haemoglobin (r=-0.12, p=0.07). Triglyceride-glucose index (r=0.76, p<0.001), homeostasis model assessment of insulin resistance (r=0.48, p<0.001), and urine albumin-to-creatinine ratio (r=0.10,p=0.05) positively correlated with glycated haemoglobin. Fasting serum insulin (r=-0.13, p=0.05), negatively correlated with triglyceride-glucose index, while homeostasis model assessment of insulin resistance (r= 0.32, p<0.001) and urine albumin-to-creatinine ratio (r=0.28, p=0.05) had a positive correlation. The estimated glomerular filtration rate was significantly positively linked with fasting serum insulin (r=0.05, p=0.05), and correlated significantly negatively with triglyceride-glucose index (r=-0.35, p=0.01), homeostasis model assessment of insulin resistance (r=-0.01, p=0.86) and urine albumin-to-creatinine ratio (r=-0.02, p=0.8). Conclusions: The triglyceride-glucose index showed a strong association with homeostasis model assessment of insulin resistance, and surpassed it in terms of predicting diabetic nephropathy in type 2 diabetes mellitus patients. Key Words: Diabetic nephropathy, Triglyceride-glucose index, Homeostasis model assessment of insulin resistance.